POTENTIAL USE OF COLTAN MINING WASTE ROCK IN ROAD CONSTRUCTION (Advances in Civil and Architectural Engineering, 2023)
The mining industry produces vast quantities of mine refuse, including waste rock and tailings, which pose a significant environmental problem. Mining residues, which are generated during ore extraction and mineral processing, are typically deposited near mines. This method of mine waste disposal can lead to environmental problems and land loss. This fact has prompted research into the utilisation of sediments as alternative materials to produce backfill and paving materials. The Democratic Republic of the Congo (DRC) possesses approximately 80 % of Africa’s coltan reserves, which is geologically unsustainable considering its many mineral resources. When coltan is extracted, geologically heterogeneous debris spanning from fine particles to boulders is produced. The purpose of this study was to analyse the potential value of mine tailings in road embankments using coltan waste rock from the eastern DRC as a case study, in accordance with the French standard. To accomplish this, it was necessary to evaluate the coltan waste rock’s chemical, mineralogical, and geotechnical properties. The coltan mining waste rock studied (SS1,i, SS2,i, and SS3,i) were found to be naturally clayey in nature, with characteristics for use in road construction. However, stabilised at 60 % by the SS4, classified as sand according to the Laboratoire Central des Ponts et Chaussées (LCPC) classification, the SS1,i, SS2,i, and SS3,i clayey waste rock possess the necessary characteristics for sub-base course materials.